TRANSFORMATIVE EDUCATION POLICIES BRIDGING THE GAP BETWEEN THEORY AND PRACTICE IN RURAL INDONESIA - Wirawati, Sri Mukti; Parancika, Rd Bily; Aris, Mohammad; Gymnastiar, Iman Ahmad; Amin, Fitrani (GoAcademica CRP, 2024)
In rural Indonesia the implementation of transformative education policies is essential for bridging the gap between theoretical frameworks and practical application. This study examines the challenges and successes associated with deploying these policies in rural settings, focusing on how they impact educational outcomes and community development. Using a mixed-methods approach, the research includes qualitative interviews with educators and policymakers, as well as quantitative analysis of educational performance data. The findings reveal significant barriers such as inadequate infrastructure, limited access to professional development, and socio-economic disparities. However, the study also highlights successful strategies that have been employed to overcome these challenges, including community involvement and context-specific adaptations. The results underscore the importance of tailored policy interventions that consider the unique needs of rural communities. This paper aims to provide actionable insights for policymakers and educators to enhance the effectiveness of education reforms in rural Indonesia.